Calibrating the Bacterial Growth Rate Speedometer: A Re-evaluation of the Relationship Between Basal ppGpp, Growth, and RNA Synthesis in Escherichia coli - Imholz, Nicole C. E.; Noga, Marek J.; van den Broek, Niels J. F.; Bokinsky, Gregory (Frontiers in Microbiology, 2020)
The molecule guanosine tetraphophosphate (ppGpp) is most commonly considered an alarmone produced during acute stress. However, ppGpp is also present at low concentrations during steady-state growth. Whether ppGpp controls the same cellular targets at both low and high concentrations remains an open question and is vital for understanding growth rate regulation. It is widely assumed that basal ppGpp concentrations vary inversely with growth rate, and that the main function of basal ppGpp is to regulate transcription of ribosomal RNA in response to environmental conditions. Unfortunately, studies to confirm this relationship and to define regulatory targets of basal ppGpp are limited by difficulties in quantifying basal ppGpp. In this Perspective we compare reported concentrations of basal ppGpp in E. coli and quantify ppGpp within several strains using a recently-developed analytical method. We find that although the inverse correlation between ppGpp and growth rate is robust across strains and analytical methods, absolute ppGpp concentrations do not absolutely determine RNA synthesis rates. In addition, we investigated the consequences of two separate RNA polymerase mutations that each individually reduce (but do not abolish) sensitivity to ppGpp and find that the relationship between ppGpp, growth rate, and RNA content of single-site mutants remains unaffected. Both literature and our new data suggest that environmental conditions may be communicated to RNA polymerase via an additional regulator. We conclude that basal ppGpp is one of potentially several agents controlling ribosome abundance and DNA replication initiation, but that evidence for additional roles in controlling macromolecular synthesis requires further study.